Self-declared attitudes and beliefs regarding protein sources are a good prediction of the degree of transition to a low-meat diet in France. (1st November 2019) - de Gavelle, Erwan; Davidenko, Olga; Fouillet, Hélène; Delarue, Julien; Darcel, Nicolas; Huneau, Jean-François; Mariotti, François
Abstract: Meat consumption in Western countries is declining and, while the proportion of strict vegetarians remains low, intermediate diets such as flexitarianism have been developing in recent years. Our objectives were to identify the different levels of transition towards low-meat diets, characterize how these diets differ in terms of food intake, and identify whether attitudes and beliefs can explain these degrees of transition. In a representative survey of the French adult population conducted in 2018 (n = 2055), participants declared whether they followed a particular diet and completed a food frequency questionnaire on 29 food sources of protein and a questionnaire on their attitudes and beliefs regarding protein sources. We identified four dietary types based on these declarative data: vegetarians, flexitarians, pro-flexitarians and omnivores. The theory of planned behavior was used to predict meat intake and intentions to reduce meat intake. The sample contained 2.5% vegetarians, 6.3% flexitarians, 18.2% pro-flexitarians and 72.9% omnivores. The diet groups displayed specific dietary profiles and attitudinal scores. Compared with omnivores, pro-flexitarians consumed less red meat, more vegetables and legumes and were much more in agreement about the environmental impacts of meat. Compared with pro-flexitarians, flexitarians consumed less red meat and processed meat, and agreed much more about the health impacts of meat. Finally, versus flexitarians, vegetarians consumed almost no meat but far more legumes, nuts and seeds, and were much more sensitive to animal welfare issues. Attitudes, social norms and perceived behavioral control (PBC) predicted intentions to reduce meat consumption but attitude was the most important predictor. Intentions and PBC were both predictive of meat consumption. The dietary type related to the level of meat intake could be predicted by self-declared attitudes and beliefs regarding protein sources.